Membrane fouling during domestic water recycling - Lodge , B. N. (Cranfield University, 2003)
The performance of a combined biological aerated filter (BAF) and an ultrafiltration (UF) system for the treatment of real and synthetic greywater, settled sewage, rainwater and borehole water has been assessed at both full-scale (at the Millennium Dome Water Recycling plant) and bench-scale. Irreversible membrane fouling was explained at bench-scale in terms of a simple but novel model whereby a proportion of the membrane area is progressively blocked, in proportion to the square root of the transmembrane pressure. This model provides a link between irreversible fouling and reversible cake filtration theory, as the predicted reduction in effective filtration area leads to increased solids loading on the unblocked area. In addition, the bulk properties (specific cake resistance and compressibility) of the filter cakes formed from biologically-treated real grey water and sewage were found to be indistinguishable. A statistical analysis of the results of longer term irreversible fouling trials at bench- scale led to numerical relationships between fouling rate and process conditions. These relationships facilitated the development of a process optimisation model, with the dual-aim of maximising output and minimising chemical consumption. At full-scale, a statistical technique was developed for calculating the relative fouling propensity of three water sources (real grey water, rainwater and borehole water) that were combined in the feed to a UP membrane. The technique was based on the relative volumes of the three sources and the mean operating trans membrane pressure. In addition, the impact of mechanical reliability on the financial viability of the full- scale plant was investigated. A Net Present Value analysis revealed that the break- even price (BEP) of the recycled water was reduced from £ 1.611m3 to £ 1.40/m 3 through increasing availability from 73.8% to 91.2%, and this can be achieved by investing in a targeted critical spares facility.